2022
DOI: 10.1186/s13643-022-02051-x
|View full text |Cite
|
Sign up to set email alerts
|

Impact of industry sponsorship on the quality of systematic reviews of vaccines: a cross-sectional analysis of studies published from 2016 to 2019

Abstract: Background Systematic reviews (SRs) provide the highest level of evidence and inform evidence-based decision making in health care. Earlier studies found association with industry to be negatively associated with methodological quality of SRs. However, this has not been investigated in SRs on vaccines. Methods We performed a systematic literature search using MEDLINE and EMBASE in March 2020. The results were restricted to those published between 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 98 publications
0
2
0
Order By: Relevance
“…Notably, our findings revealed that unfunded and government‐funded reviews exhibited higher reporting quality compared to industry‐funded studies and those without declared funding, although the reasons for this observation are not immediately apparent. Previous studies have reported similar results, finding that industry‐funded systematic reviews may be associated with lower methodological quality in a number of topics, including vaccination,[37] drugs and medical devices [38] and asthma treatment [39]. Gøtzsche et al (2012) proposed that the higher quality of nonindustry reviews was due to the larger number of co‐authors who are methodologists [40].…”
Section: Discussionmentioning
confidence: 84%
“…Notably, our findings revealed that unfunded and government‐funded reviews exhibited higher reporting quality compared to industry‐funded studies and those without declared funding, although the reasons for this observation are not immediately apparent. Previous studies have reported similar results, finding that industry‐funded systematic reviews may be associated with lower methodological quality in a number of topics, including vaccination,[37] drugs and medical devices [38] and asthma treatment [39]. Gøtzsche et al (2012) proposed that the higher quality of nonindustry reviews was due to the larger number of co‐authors who are methodologists [40].…”
Section: Discussionmentioning
confidence: 84%
“…We have a reporting guideline for systematic reviews and its extensions [43], as well as Cochrane's methodological expectations for systematic reviews of interventions [44], Joanna Briggs Institute (JBI) Checklist for Systematic Reviews [45], AMSTAR 2 tool for assessing methodological quality [5], a ROBIS tool for assessing the risk of bias in systematic reviews [46], etc. However, despite the existence of those tools, it has been reported in multiple studies that published systematic reviews do not adhere to guidance from those tools [47][48][49][50][51][52]. Thus, further studies in the field of research methodology should explore interventions that would improve how systematic reviews are planned, conducted, and reported.…”
Section: Exploring Interventions For the Adoption Of Methodological A...mentioning
confidence: 99%